A inclusão do estudante com deficiência intelectual na educação superior do IFRS Bento Gonçalves : um olhar sobre a mediação docente - Accorsi, Maria Isabel (My University, 2016)
This dissertation aims to analyze the process of inclusion of a student with intellectual disabilities (ID) in the Technological Higher Education of the Federal Institute of Education, Science and Rio Grande Technology South Campus Bento Gonçalves, with a focus on teaching mediation. The theoretical contribution was made by the concept of the study and intellectual disability characteristics, with support of authors like Mantoan (2006) and Pletsch (2014); on concepts and reflections of inclusive education in the context of basic education and higher education, with Carvalho (2009), Baptist (2002), Beyer (2010), Magellan (2006) and Mittler (2003); and the contributions of Vygotsky for education, based on its work on Defectology and mediation, with the support of authors as Rego (2012), La Taille (1992) and Beyer (1996). To perform this qualitative research was conducted an investigation using as a case study strategy, composed of semi-structured interviews and document analysis. Therefore were heard seven teachers who teach for students with ID and the student himself. The main documents of the institution that approach the issues of access and retention of people with a disability in higher education Have also been analyzed. The data obtained in the interview with the teachers were organized into three categories that enabled a more detailed analysis of the speeches: design of learning, teaching action and interaction. Data analysis was based on Bardin content analysis (2000). The documents and the interview with the student were analyzed, summarized and integrated into the analysis of the three categories. The results of the study demonstrated the difficulty that the presence of a student with DI in higher education sets off in the teaching process, already consolidated, teachers. Also reveals that some changes are needed in the teacher's pedagogic action so that the teaching mediation happen. The conclusion establishes the importance of teaching mediation in the classroom to promote learning of the intellectual disabled student and identifies the teacher's mediation can be thought from the interweaving of a conception of learning to understand the possibility of building alternative pathways learning and development of people with a disability and a teacher planned action, that seeketh favor the student in the learning process by means of intentional, continuous and builders interactions.
Esta dissertação tem como principal objetivo analisar o processo de inclusão de um estudante com deficiência intelectual (DI) na Educação Superior Tecnológica do Instituto Federal de Educação, Ciência e Tecnologia do Rio Grande do Sul, Campus Bento Gonçalves, tendo como foco a mediação docente. O aporte teórico foi constituído pelo estudo do conceito e características da deficiência intelectual, com sustentação de autores como Mantoan (2006) e Pletsch (2014); sobre conceitos e reflexões da educação inclusiva no contexto da educação básica e da educação superior, com Carvalho (2009), Baptista (2002), Beyer (2010), Magalhães (2006) e Mittler (2003); e nas contribuições de Vygotsky para educação, amparada em seus trabalhos sobre a Defectologia e a Mediação, com apoio de autores como Rego (2012), La Taille (1992) e Beyer (1996). Para executar essa pesquisa de ordem qualitativa, conduziu-se uma investigação utilizando como estratégia um estudo de caso, composto por entrevistas semiestruturadas e análise de documentos. Para tanto, foram ouvidos sete professores que lecionaram disciplinas para o estudante com DI e o próprio estudante. Também foram analisados os principais documentos da instituição que abordam as questões do acesso e da permanência de pessoas com deficiência na educação superior. Os dados obtidos na entrevista realizada com os professores foram organizados em três categorias que viabilizaram uma análise mais detalhada das falas: concepção de aprendizagem, ação docente e interação. A análise dos dados foi realizada com base na análise de conteúdo de Bardin (2000). Os documentos e a entrevista com o estudante foram analisados, resumidos e integrados às análises das três categorias. Os resultados obtidos no estudo demonstraram a dificuldade que a presença de um estudante com DI na educação superior desencadeia no processo de ensino, já consolidado, dos professores. Também revelou que algumas mudanças são necessárias na ação pedagógica do professor para que a mediação docente aconteça. A conclusão estabelece a importância da mediação docente em sala de aula para promover a aprendizagem do estudante com deficiência intelectual e identifica que a mediação docente pode ser pensada a partir do entrelaçamento de uma concepção de aprendizagem que compreenda a possibilidade da construção de vias alternativas para a aprendizagem e desenvolvimento de pessoas com deficiência e de uma ação docente planejada, que busque favorecer o aluno no seu processo de aprendizagem por meio de interações intencionais, contínuas e edificadoras.
Keywords: Vigotsky, Lev Semenovich, 1896-1934; Educação inclusiva; Educação especial; Mediação; Ensino superior - Métodos de ensino; Deficiência mental - Educação; Special education; Mediation; Education, Higher - Teaching methods; Mental retardation - Education; Inclusive education